Peran Penyuluh Agama Di Kecamatan Kasihan Dalam Menghadapi Isu Ekstremisme Keagaan - Hamidah Az-Zahra S Lubis (FAI UMY, 2017)
Peran Penyuluh Agama Di Kecamatan Kasihan Dalam Menghadapi Isu Ekstremisme Keagaan